2009
DOI: 10.1038/jhh.2009.91
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction is associated with increased levels of biomarkers in essential hypertension

Abstract: To assess the correlation between endothelial dysfunction and the serum levels of biomarkers of inflammation, remodelling and oxidative stress in essential hypertension, 78 treatment-naïve essential hypertensives (mean age 43 years) underwent measurement of endothelial dysfunction, using the maximal acetylcholine-induced forearm vasodilation and serum levels of adhesion molecules, selectins, chemokines, metalloproteinases, copper, zinc, selenium, vitamins, homocysteine, malondialdehyde, erythrocyte glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 34 publications
3
29
1
2
Order By: Relevance
“…A previous study reported that the urine levels of 8-OHdG decreased after treatment in the ARB group, but did not decrease in the non-ARB group in hypertensive patients [15]. MDA and 4-HNE, the secondary products of lipid peroxidation, are involved in lipid-related oxidative stress, which leads to vascular injury in hypertension [21,22].…”
Section: Measurements Of Serum Estradiol and Testosteronementioning
confidence: 96%
“…A previous study reported that the urine levels of 8-OHdG decreased after treatment in the ARB group, but did not decrease in the non-ARB group in hypertensive patients [15]. MDA and 4-HNE, the secondary products of lipid peroxidation, are involved in lipid-related oxidative stress, which leads to vascular injury in hypertension [21,22].…”
Section: Measurements Of Serum Estradiol and Testosteronementioning
confidence: 96%
“…Since NO has the ability to inhibit the expression of MCP-1, in endothelial dysfunction MCP-1 and leukocyte migration are activated, increasing inflammation in the vascular wall. elevated concentrations of MCP-1 have been described in patients with essential hypertension and endothelial dysfunction [44]. asymmetric dimethylarginine (adMa) is an endogenous inhibitor of NO synthase which, through a reduction in its bioavailability, can lead to endothelial dysfunction.…”
Section: Chemokines and Endothelial Dysfunctionmentioning
confidence: 99%
“…Two main adverse clinical consequences of OxS are endothelial dysfunction and left ventricular hypertrophy [175]. Therefore, new strategies in reversing both these adverse conditions by targeting OxS by novel means are promising ways to improve the prognosis of CKD patients.…”
Section: Renal Function and Oxsmentioning
confidence: 99%